Digital Code-Mixing among Ethiopian Youth: Attitudes toward English Loanwords in Social Media Communication - Sofia Martínez (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2010)
Social media communication has transformed language practices worldwide, fostering increased code-mixing and the adoption of English lexical items in multilingual communities. Among Ethiopian youth, English loanwords frequently appear in digital interactions across messaging platforms and social media networks. This study investigates how Ethiopian youth perceive and use English loanwords in digital communication, focusing on their sociolinguistic attitudes and motivations for code-mixing. Using a quantitative survey design, data were collected from 410 urban youth aged 16–24 through a structured questionnaire measuring language attitudes and digital language practices. Exploratory factor analysis and descriptive statistics were employed to identify attitudinal dimensions and usage patterns. The results indicate strong acceptance of English loanwords, primarily due to their perceived association with modernity, efficiency, and global connectivity. Three attitudinal dimensions were identified: Prestige, Integration, and Linguistic Purism. While most participants acknowledged the cultural value of local languages, they reported frequent use of English lexical items in informal digital contexts to enhance expressiveness and social identity. English loanwords have become integral elements of youth digital discourse in Ethiopia, reflecting broader processes of linguistic globalization and identity negotiation. Future research should incorporate corpus-based analysis of social media data to better understand real-life patterns of digital code-mixing and language evolution.